Change of TGF-β1 Gene Expression and TGF-β1 Protein Level in Gingival Crevicular Fluid and Identification of Plaque Bacteria in a Patient with Recurrent Localized Gingival Enlargement before and after Gingivectomy - Lilies Anggarwati Astuti; Mochammad Hatta; Sri Oktawati; Rosdiana Natzir; Ressy Dwiyanti (Case Reports in Dentistry)
This case report highlights the change of TGF-β1 gene expressions and TGF-β1 protein level in gingival crevicular fluid (GCF) and identification of plaque bacteria in a patient with recurrent localized gingival enlargement before and after gingivectomy treatment. A 26-year-old woman came to AG Dental Care Clinic, South Sulawesi, Indonesia, in October 2015 with a chief complaint that her gingiva often bled spontaneously and she felt pain on her gingiva and felt less comfortable and no self-confidence with her anterior and posterior gingival condition on the right maxilla region which is slightly larger than normal. She often felt that her gingiva could bleed spontaneously when she was talking or remains silent though. The patient is disturbed by the malodor she felt. At that moment, the patient sought for gingivectomy treatment. Three years afterward, the patient came back with the same complaint. Gingival crevicular fluid has been taken from the gingival sulcus before and after gingivectomy. Clinical and GCF follow-up examination was performed one week and three weeks after gingivectomy, and successful results on biological, functional, and aesthetic parameters were observed.